Modernisasi Pendidikan Islam Perspektif Said Nursi - Habib Zainuri; Khojir Khojir; Mukmin Mukmin (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2023)
In the midst of the dynamics of globalization and technological advances, new challenges and opportunities arise, requiring renewal and modernization in the approach to Islamic education. This research aims to provide a critical review of the modernization of Islamic education, especially in the context of curriculum transformation and learning methodology. Beiduzzaman Said Nursi has a concept of modern Islamic Education. that Said Nursi's thoughts on education have been updated by combining religious principles with modern theories. According to Nursi, humans are only meaningful if they are bound and dependent on God, so that the human ability to think about nature is the result of God's light. It is on this basis that all science arises for the sole purpose of studying the signs of God's power and is a science with a religious spirit. This eliminates the bias against religion and contemporary science, both of which secularism instills.